Does conservation agriculture work as advertised? Implications on labor and farm returns in sentinel sites in Malawi and Zambia - Chikwalila, Eric Muhulu; Ngoma, Hambulo; Pangapanga-Phiri, Innocent; Tufa, Adane H.; Alene, Arega D.; Chikoye, D.; Chipindu, Lovermore; Simutowe, Esau; Marenya, Paswel P.; Thierfelder, Christian (CGIAR, 2023)
Sub-Sahara Africa (SSA) has degraded soils, epitomized by decades of loss of valuable topsoil caused by continuous cultivation, monocropping, excessive run-off, and the absence of effective conservation-based farming practices. Conservation Agriculture (CA) offers several opportunities to restore land and arrest soil degradation in smallholder farming systems of SSA. This study assessed labor productivity and farm returns associated with CA in Malawi and Zambia using household survey data collected from 500 and 616 farmers in Zambia and Malawi, respectively. Half of the sample was drawn from areas known to have had intense CA promotion over the last 10 years since 2023, hereafter called treatment areas. The other half came from control areas where there was no known institutional CA promotion. We studied the effects of CA on maize, groundnut, and soybean. The study found yield under CA statistically higher than under conventional, suggesting that CA improves yield. The study also observed that CA saves farmers’ time, where households in the non-CA areas allocate 26.00 and 21.59 more personal days per season per hectare than households in the treatment areas in Malawi and Zambia, respectively. Based on the two-stage robust stochastic frontier analysis, study findings revealed that CA enhances labor productivity by 3.72% and 2.75 % in Malawi and Zambia, respectively. Likewise, CA improves farm productivity by 13.90 % and 8.80 % in Malawi and Zambia, respectively. Gross margin analysis results suggest farmers in the treatment areas have higher gross margins of US$ 1,474.6 per ha than farmers in control areas with US$ 813 per ha in Malawi. Similarly, farmers in the treatment areas in Zambia had higher gross margins at US$ 764 per ha compared to US$ 394 per ha in control areas. These positive economic benefits in this paper render credence to continued support for CA promotion but more multi-location and multi-year research building on panel surveys is required to further assess the socioeconomic benefits of CA. More work remains on understanding appropriate policy and economic incentives that can be used to spur adoption and how to effectively strengthen extension systems to better support CA promotion and scaling.